Impact of an autologous oxygenating matrix culture system on rat islet transplantation outcome. (June 2015) - Schaschkow, A.; Mura, C.; Bietiger, W.; Peronet, C.; Langlois, A.; Bodin, F.; Dissaux, C.; Bruant-Rodier, C.; Pinget, M.; Jeandidier, N.; Juszczak, M.T.; Sigrist, S.; et al.
Abstract: Disruption of the pancreatic islet environment combined with the decrease in oxygen supply that occurs during isolation leads to poor islet survival. The aim of this study was to validate the benefit of using a plasma-based scaffold supplemented with perfluorodecalin to improve islet transplantation outcome. Rat islets were cultured in three conditions: i) control group, ii) plasma based-matrix (P-matrix), and iii) P-matrix supplemented with emulsified perfluorodecalin. After 24 h culture, matrix/cell contacts (Integrinβ1, p-FAK/FAK, p-Akt/Akt), survival (caspase 3, TUNEL, FDA/PI), function, and HIF-1α translocation were assessed. Afterwards, P-matrices were dissolved and the islets were intraportally transplanted. Graft function was monitored for 31 days with glycaemia and C-peptide follow up. Inflammation was assessed by histology (macrophage and granulocyte staining) and thrombin/anti-thrombin complex measurement. Islet survival correlated with an increase in integrin, FAK, and Akt activation in P-matrices and function was maintained. Perfluorodecalin supplementation decreased translocation of HIF-1α in the nucleus and post-transplantation islet structure was better preserved in P-matrices, but a quicker activation of IBMIR resulted in early loss of graft function. "Oxygenating" P-matrices provided a real benefit to islet survival and resistance in vivo . However, intraportal transplantation is not suitable for this kind of culture due to IBMIR; thus, alternative sites must be explored.